SEASONAL MOVEMENT IN THE CONSUMPTION OF MEAT IN BENGHAZI - S. Mukorji; A. Yamani; Hawaiw, Abdessalam (Dirasat in Economics and Business, 1969)
Agricultural commodities generally exhibit market variations within a year. In certain months in a year the production of a given commodity is more than in other months. Meat, though not an agricultural commodity itself, shows a set pattern of variation over the seasons. Breeding, live-stock feed and available number of animals in marketable shape all depend on seasons.